OpenStack administration with Ansible 2 : orchestrate and automate your OpenStack cloud operator tasks with Ansible 2.0 /: orchestrate and automate your OpenStack cloud operator tasks with Ansible 2.0. (2016) - Bentley, Walter
No abstract available